Impact of Sweat Absorption on the Electrostatic Potential Build-Up in Cotton and Nylon Fabric Samples (Journal of Fiber Bioengineering and Informatics, 2022)
Natural and synthetic fibers can be significant sources of electrostatic build-up in garments. The intrinsic electrical properties of fibers are the result of their chemical composition and polymer structure. Factors such as moisture, temperature, and friction intensity can influence these properties. Due to the insulative characteristics of most fibers, fabrics keep their charge for relatively long periods. This can lead garments to cling to each other, attract dust particles, and create potential hazardous discharge shocks. Moisture increases the electrical conductivity of fibers that leads to a decrease in the build-up of electrostatic potential. The purpose of this study was to identify the impact of absorption of distilled water and electrolyte solution on fabric conductivity and subsequent electrostatic build-up. The study consisted of three components: 1, Comparison of the intrinsic electrical resistance of distilled water to electrolyte solution. 2, Assessment of the electrical resistance of cotton and Nylon fabric samples in relation to decreasing levels of fluid retention. 3, Determination of the electrostatic build-up in Cotton and Nylon fabric samples for dry and wet conditions. The results showed that cotton absorbed more distilled water and electrolyte solution than Nylon. However, the reduction in electrostatic build-up was similar for both. The results indicate that body sweat (electrolyte) can substantially reduce the electrical resistance characteristics of both natural and synthetic fibers and can substantially reduce the generation of electrostatic potential in garments.